An adjustable pre-stress based sensitivity enhancement scheme for cantilever-based resonant sensors. (1st January 2021) - Zhao, Ziqi; Wang, Dong F.; Lou, Xueqiao; Ono, Takahito; Itoh, Toshihiro
Highlights: A sensitivity enhancement scheme is proposed for cantilever-based resonant sensors. The idea is magnetically applying a pre-stress to achieve larger frequency offset. A new pressure sensing prototype device is designed to verify the validity. The pre-stress can be adjusted by simply applying different magnetic forces. The sensitivity is enhanced by optimizing position and range of the pre-stress. Abstract: A new sensitivity enhancement scheme, mainly comprised of a harmonic oscillator and a set of magnetic material, is proposed for desirable applications in cantilever-based resonant sensors. The basic idea is to magnetically apply a pre-stress on the harmonic oscillator to achieve a larger frequency offset. The applied axial pre-stress, which varies the equivalent stiffness of the harmonic oscillator, is simulated by an adjustable magnetic force. The resonant frequency is accordingly increased with a larger offset to a certain mass or force, thus enhancing the sensitivity of the harmonic oscillator. A new pressure sensing prototype device, mainly comprised of a triple-beam tuning fork (TBTF), a pressure sensitive film, a set of magnetic and piezoelectric materials, is designed to both theoretically and experimentally verify the validity of the sensitivity enhancement scheme for cantilever-based resonant sensors. The pre-stress can be adjusted by simply applying different magnetic forces. And the sensitivity of the cantilever-based resonant sensors can be further enhanced by optimizing both the position and the magnitude of the pre-stress.